Innovative ICG Application in Benign Gynaecological Surgery: Enhancing Safety and Precision - Summer Deah Menezes; Tanushree Rao (Case Reports in Obstetrics and Gynecology)
In the context of increased adoption of minimally invasive surgery for benign gynaecological conditions, this study underscores the paramount importance of patient safety. We explored the efficacy of indocyanine green (ICG), a fluorescent dye, in enhancing the visualisation of critical anatomical structures during complex laparoscopic procedures. Our methods involved the direct administration of ICG into the ureters for precise identification and dissection, as well as an innovative vaginal application to delineate the rectovaginal plane in cases with distorted pelvic anatomy. The study presented two cases: a laparoscopic hysterectomy for a multifibroid uterus and a case of advanced endometriosis with rectal involvement. Results indicated that ICG use significantly improved real-time visualisation of the ureters and the rectovaginal plane, which facilitated the surgeries and reduced the cognitive load on surgeons. There were no intraoperative complications, and the postoperative phase showed positive patient outcomes. In conclusion, the application of ICG in these laparoscopic surgeries proved to be a beneficial adjunct, suggesting its potential for broader application in benign gynaecological surgeries. Future research is warranted to explore additional uses of ICG, with a focus on enhancing patient safety and surgical efficacy.